WAS SOCRATES’ DEATH A TYPE OF CALVARY? - Dimgba Dimgba Esowe; Emmanuel E. Etta; Offiong O. Asuquo (European Scientific Journal, ESJ, 2013)
About four hundred years before Christ, a philosopher and moral giant named Socrates was convicted to death in Athens, Greece, by a jury. He and his friends believed the judgement was prejudiced against him due to his way of life which was seen as a threat to the evil ways of the elite in the society. Crito, a wealthy friend of his, made arrangements for his escape from prison but he refused. On the day of his execution, he accepted and drank poison. He died. In applauding that decision, Ziniewicz (2011) asserts that Socrates‟ death changed the course of things in the world for the better, that without that, he would not have been born. On the other hand, the Bible says that while we were yet sinners Christ died for us. Since the time of Christ‟s first advent into the world, records of dates of events are stated as either B. C. or A. D. which are acronyms meaning Before Christ or in the year of the Lord. Was Socrates death then a type of Calvary? God who created the world and directs the affairs herein, gave humanity sacrificial types in animal symbols, thus he tested and yet forbade Abraham from offering Isaac. Socrates had a way of escape made for him but he chose to die out of self pride. The Athenians did not need his death for their freedom. It is who the Son of God, Jesus Christ sets free that is free indeed. Socrates was born a sinner, Christ was born sinless. Socrates had no divine prophecies guiding his activities, but actual types of Christ and His mission had divine utterances guiding their operations. Thus, it cannot be said that the death of Socrates was a type of Calvary where Christ died to set men free from sin and destruction.